(3CYjGf GdYUQ hCYhGf GdfUQs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3MQa GdYjf YGeQ Hf eMeO Hf Ydi Hf hgH s
(3BNQgG (B:s
(3YHO GdeMehO Hf YHO GdSdGe Hf MGJe hcGf jOYi Gfg ef PQjI CHj aQGS Hf MeOGf s
(3jHJOF HChd MQa GdYjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B25 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI CjGUhajG (B(2966) s
Keywords: (3GdJGQjNs